Efek Antibakteri Kombinasi Dekokta atau Ekstrak Metanol Daun Syzygium polyanthum dengan Kloramfenikol pada Staphylococcus aureus dan Escherichia coli secara In Vitro - Nuryanti Fardila (Jurnal Kedokteran Komunitas (Journal of Community Medicine), 2019)
Background: A combination between herbs and antibiotic ingredients could become a breakthrough application within endurance therapy upon chloramphenicol usage. Antibacterial features derived from bay leaves are executable both in cellular wall and intracellular system. The combination effect between methanol extract of bay leaf and chloramphenicol intracellular antibiotics decoction will be assessed in this research using zone of inhibition test of S. aureus and E. coli.Method: Inhibition zone will be tested by utilizing modified Ameri-Ziaei Double Antibiotic Synergism Test (AZDAST) method. The variables were divided into 5 groups consisting high and low dosages of chloramphenicol (HDA and LDA), high and low dosage of Bay leaves methanol extract (HDHm and LDHm), high and low dosages of Bay leaves decoction (HDHd and LDHd), the methanol extract of bay leaves and chloramphenicol combination (CSMC), and bay leaves decoction-chloramphenicol (CSDC) compound in S. aureus and E. coli. The inhibition zone will be analyzed by Mann-Whitney test with significance level value of p<0.05.Results: In S. aureus and E. coli, CSDC show not distinguishable effect compared to the single use of antibiotic. Similar results were generated in CSMC in S. aureus and E. coli.Conclusion: The combination of bay leaves decoction and methanol extract did not increase the inhibition of S. aureus and E. coli Keywords: Antibiotic resistance, Bay leaves, chloramphenicol, Staphylococcus aureus, Escherichia coli